2021
DOI: 10.1167/tvst.10.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Retina Vascular Perfusion Dynamics During Exercise With and Without Face Masks in Healthy Young Adults: An OCT Angiography Study

Abstract: To determine possible impacts on retinal microvasculature in healthy young adults during exercise with a face mask, using optical coherence tomography angiography (OCTA). Methods: Twenty-three healthy participants (23 eyes, 17 women and 6 men) performed the incremental continuous running test (ICRT) with different masks. OCTA of the macula and optic nerve head were performed before and after ICRT to detect changes in retinal vessel density (VD). All participants were in groups A, B, and C (before ICRT) and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Most included studies were randomized crossover studies ( n = 42), while two studies were randomized controlled trials [ 24 , 25 ] and one study used a non-randomized repeated measure [ 26 ]. Except for three studies that involved children [ 27 – 29 ], all the other studies involved adults, including athletes ( n = 3) [ 30 – 32 ], recreational athletes ( n = 2) [ 33 , 34 ], and healthy adults ( n = 37) [ 3 , 12 – 15 , 18 , 24 – 26 , 35 – 62 ], with a total of 1264 participants (708 men, 556 women) included. Overall, 37 studies included both men and women, while eight included only men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most included studies were randomized crossover studies ( n = 42), while two studies were randomized controlled trials [ 24 , 25 ] and one study used a non-randomized repeated measure [ 26 ]. Except for three studies that involved children [ 27 – 29 ], all the other studies involved adults, including athletes ( n = 3) [ 30 – 32 ], recreational athletes ( n = 2) [ 33 , 34 ], and healthy adults ( n = 37) [ 3 , 12 – 15 , 18 , 24 – 26 , 35 – 62 ], with a total of 1264 participants (708 men, 556 women) included. Overall, 37 studies included both men and women, while eight included only men.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 22 studies used a progressive exercise test [ 3 , 12 , 14 , 18 , 24 , 26 , 30 , 35 , 36 , 39 , 41 , 43 – 45 , 48 , 50 , 51 , 53 – 55 , 59 , 60 ], while 19 employed the steady-state constant exercise test [ 13 , 15 , 25 , 29 , 31 , 34 , 37 , 38 , 40 , 42 , 46 , 47 , 49 , 52 , 56 58 , 61 , 62 ], and two used interval exercise tests [ 28 , 32 ]. Moreover, one study used a resistance exercise test [ 33 ], and one used a sit-to-stand test [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: CI, confidence interval; SD, standard deviation; SpO 2 , oxygen saturation level; Std. mean diff., standard mean difference [ 4 , 5 , 10 , 11 , 12 , 13 ].…”
Section: Figurementioning
confidence: 99%
“…A study conducted by Hua D et al showed that these changes, associated with CO2 retention, reduced the retinal vessel density (VD) in the superficial plexus even under quiescent conditions, which might have clinical implications for protecting healthy and indoor manual labor workers from potential risksdue to prolonged face mask use. 8 Their impacts on the retinal vessels are envisioned by the high resolution of spectral-domain optical coherence tomography (HR-SDOCT), which permits also the measurement of retinal vessel diameters and choroidal thickness. 9 In the present study, we aimed at investigating whether prolonged N95 respirators or surgical masks wearing induce retinal vessel diameters and choroidal changes visualized with HR-SDOCT.…”
Section: Introductionmentioning
confidence: 99%